Gay, lesbian, bisexual, and transgender aging : challenges in research, practice, and policy - Eyler, A. Evan; Witten, Tarynn (Johns Hopkins University Press, 2011)
This volume address the challenges of aging in the gay, lesbian, bisexual, transgender, and intersex populations, presenting what is currently known about aging GLBT individuals and what services are needed to support them. The editors first provide an introductory overview comparing caregiving in GLBT and normative aging communities. In chapters devoted to the issues of each alternative sexuality and gender identity community, top experts in the field discuss biomedical, psychological, social/sexual, spiritual, socioeconomic, and service topics related to that community's aging needs. By using a combination of the latest biological and social science research, moving case studies and first-person accounts, practical advice for health professionals, and research literature citations, this book addresses the major concerns of aging GLBT populations.